2021
DOI: 10.1002/hlca.202100053
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Recent Advances in the Synthesis of Organic Unsymmetrical Disulfides

Abstract: Organic unsymmetrical disulfides have been extensively applied in various academic and industrial fields including intermediates in organic synthesis, agriculture, and food science, natural materials, biochemistry, pharmaceutical and medicine chemistry, polymers, material engineering, etc. They play a crucial role in the fabrication of various biological active sulfur heterocycles. Due to broad and extensive applications, many methods have been developed for the synthesis of unsymmetrical S−S and efforts have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…Based on the control experiments and related literatures, [10,14d,20] we proposed a possible mechanism for this reaction (Scheme 3). Initially, compound 1 a reacted with CH 3 OH under the action of base to form A , and A was isomerized into B in the presence of base.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the control experiments and related literatures, [10,14d,20] we proposed a possible mechanism for this reaction (Scheme 3). Initially, compound 1 a reacted with CH 3 OH under the action of base to form A , and A was isomerized into B in the presence of base.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the important role of disulfides in various fields, the synthesis of disulfides has attracted the interest of many chemists [10,11] . Though a couple of ways to synthesize symmetrical disulfides have been developed previously, the synthesis of unsymmetrical disulfides is comparatively undeveloped.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, chemists have worked on designing and synthesizing various asymmetric disulfides. However, most of the literature reported that the reaction was carried out using thiol as a substrate, with a bad smell and low commercial value . Thus, considerable efforts had been spent to develop alternative reagents as S-S sources to synthesize disulfides, for example, RSSSSR, RSSLG, NuSSNu, RSSAc, and RSSTs (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the main challenge is avoiding the generation of significant amounts of symmetrical by-products. Therefore, known procedures generally employ two thiols with obvious difference in the abilities to be oxidized, 22–28 or pre-converting one thiol to stable electrophilic agents, such as sulfenamides, 29,30 thiosulfonates 31 and organophosphorus sulfenyl derivatives. 32,33 Sulfenyl chloride intermediates have been investigated in situ and used for asymmetrical disulfides synthesis.…”
mentioning
confidence: 99%